Improving Citizen’s Awareness in Conserving Diversity of Malay Traditional Dances in Malaysia through the Art Appreciation Performed by Students of Early Childhood Education Study Program - Watini, Sri; Aini, Qurotul; Hardini, Marviola; Rahardja, Untung (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to describe the variants of Malay traditional dances in Malaysia. Melayu cultures are spread over several locations including Malay Peninsula, Borneo, West Kalimantan, Sumatera, Thailand, Burma, Singapore, Sarawak, Sabah, and the other small islands. Malay is one of the ethnic of Austronesian people and, to these days, it keeps Austronesian heritage. The Austronesian cultures between the areas share some similarities. Through the result of this study, the researcher hopes that the awareness in conserving cultures, according to the special local traditions and characteristics possessed by every country which falls into ‘Malay country, would be increased, so that disunities and conflicts can be prevented. The education for ‘Malay younger generations, which teaches that cultural diversity should be recognized as the treasure of this world, must be implemented so that they would be able to maintain the cultures of their countries. This was an ethnographic study that was conducted qualitatively. The ethnographic study is usually about social communities, faiths, beliefs, as well as traditions, including traditional dances. This study was conducted in Shah Alam, Malaysia. The data of this study were collected by using a method so-called field observation, open and in-depth interview, direct interaction with the concerned society and the art show performed by the students of the early childhood education program of MSU PTPL Malaysia. The findings of this study implied that Malaysia possessed 7 variants of ‘Malay traditional dances with different characteristics.